2010
DOI: 10.1007/s11998-010-9242-9
|View full text |Cite
|
Sign up to set email alerts
|

On the stress distribution at scratching of thin film structures

Abstract: Scratching of thin film/substrate structures is studied theoretically and numerically. In most cases, the material behavior of the film as well as the substrate is described by classical elastoplasticity accounting for large deformations; further, pressuresensitive flow models are considered. The main efforts are devoted toward an understanding of the influence from the film/substrate boundary on the stress distribution at scratching but for comparative reasons, scratching of homogeneous materials are also stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…Further developments regarding this matter were presented by Wredenberg and Larsson. 33 In reference (33), the details concerning the stress fields at thin film scratching were analyzed and it was concluded that high shear stresses were the driving force for both crack initiation and continued growth along the film/substrate interface. In this investigation, the load at crack forming and subsequent growth is not of immediate interest but instead, the stability of delamination growth in such a situation is studied.…”
Section: Delamination Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Further developments regarding this matter were presented by Wredenberg and Larsson. 33 In reference (33), the details concerning the stress fields at thin film scratching were analyzed and it was concluded that high shear stresses were the driving force for both crack initiation and continued growth along the film/substrate interface. In this investigation, the load at crack forming and subsequent growth is not of immediate interest but instead, the stability of delamination growth in such a situation is studied.…”
Section: Delamination Analysismentioning
confidence: 99%
“…Also, thin film scratching has been studied quite frequently, cf., e.g., references (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) considering different aspects of the problem such as fracture, delamination, the behavior of different global and local scratch variables (global scratch variables include normal and tangential hardness, apparent coefficient of friction and contact area) and alternative constitutive behavior. In reference (33), the local stress fields at thin film scratching were examined in some detail and an important conclusion from this study was that high shear stresses are the dominant factor leading to delamination initiation and growth.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Os modos de falha associados com o ensaio de riscamento têm sido identificados com base em observações e análise do sulco gerado durante o teste [15,16,37,38,42,48,49,51,[53][54][55][56][57][58]. Desta forma, alguns modos de falha envolvem o destacamento do revestimento do substrato, sendo, portanto, de importância direta durante uso do ensaio de riscamento como avaliação da adesão.…”
Section: Modos De Falha Dos Sistemas Revestidos No Ensaio De Riscamentounclassified